Impact of Corticosteroids on the Proportions of Circulating Tfh Cell Subsets in Patients With Systemic Lupus Erythematous - Mao, Minjing; Xu, Shuqin; Lin, Lin; Dong, Danfeng; Xue, Minghui; He, Siwei; Cai, Gang (Frontiers in Medicine, 2022)
Objectives This study aimed to analyze the distribution of T follicular helper (Tfh) cells in lupus patients, and the effects of steroids on circulating Tfh cells. Methods Circulating Tfh cell subsets were defined by multicolor flow cytometry as Tfh17, Tfh2 or Tfh1 subpopulations of CXCR5+CD45RA–CD4+ T cells in the peripheral blood of SLE patients and healthy controls. To test the effects of corticosteroid on Tfh cells, PBMC harvested from both SLE and healthy controls were cocultured with dexamethasone, and then analyzed by Flow cytometry. Results The proportion of Tfh17 cells in SLE patients was increased significantly compared with healthy controls. Additionally, patients with an active disease had reduced Tfh1 subsets than those with an inactive disease and healthy controls. The frequency of Tfh2 cells was associated with the proportion of circulating plasmablasts and the amount of anti-dsDNA. Dexamethasone reduced the percentage of Tfh2 cells while increased the proportion of Tfh17 subset in gated CXCR5+CD45RA–CD4+ T cells. Conclusion Our study investigated the distribution of circulating Tfh subsets in lupus patients. Corticosteroids treatment not only down-regulated the proportion of circulating Tfh cells, but also altered the distribution of Tfh subsets in vivo and in vitro.